EXPLORING THE IMPACT OF LEADERSHIP STYLES ON EMPLOYEE JOB PERFORMANCE - A CASE STUDY OF EMPLOYEES IN VIETNAMESE ENTERPRISES - Lin, Linda Lin-Chin; Viet , Nguyen-Van (Graduate Program of Universitas Tarumanagara, 2025)
This study explores the impact of leadership styles on employee job performance in Vietnamese enterprises, focusing on authoritarian, democratic, and laissez-faire leadership styles. Through a questionnaire survey, 298 valid responses were collected and analyzed using SPSS 25.0, including descriptive statistics, reliability analysis, t-tests, ANOVA analysis, correlation analysis, and regression analysis.The findings indicate: (1) Authoritarian leadership has a significant negative impact on employee job performance; (2) Democratic leadership has a significant positive impact on employee job performance; (3) Laissez-faire leadership has a significant positive impact on employee job performance. This study emphasizes the flexible use of leadership styles to improve employee performance and suggests the reasonable application of democratic and laissez-faire leadership to foster responsibility and creativity among employees, ultimately enhancing company competitiveness and long-term growth.